(3OjhGf GHj aQGS GdMeOGfjs - (3CHh aQGS , GdMGQK Hf SYjO Hf MeOGf GdJZdHj GdQHYj, CHhaQGS GdMeOGfj,J (B357 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI hGdOjHGLI GdTYQ hOjhGf GdYQH GHOkG hYfhGf GdGOH s
(3BNQgG (B:s
(3hbGd(B: (3GfXQ dVYaj jG bhj hcf dabQj jG Zfj CMSf Zdi aEffj YHO Edi faSj efSj s
(3Vef eLehY , JQJjHgG (B: 1s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B156s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3eJaQbGJs